Single Inverter Fed Speed Sensorless Vector Control of Parallel Connected Two Motor Drive. (1st January 2016) - Gunabalan, R.; Subbiah, V.
Abstract : This paper describes a speed sensorless vector control method of the torque for cost-effective parallel-connected dual induction motor fed by a single inverter. A natural observer with load torque adaptation is employed to estimate the speeds of the same rating induction motors connected in parallel and fed by a single inverter. The speed difference between the two induction motors for unbalanced load conditions is less in natural observer than the conventional adaptive rotor flux observer. Direct field oriented control is used to calculate the rotor angle from the estimated rotor fluxes and the mean rotor flux is kept constant by rotor flux feedback control. The simulation and experimental results of studies are demonstrated for various running conditions to prove the effectiveness of the proposed method. The closed loop speed control operation with inner current control was performed by TMS320F2812 processor.